2014
DOI: 10.1007/s13318-014-0220-y
|View full text |Cite
|
Sign up to set email alerts
|

The preclinical pharmacokinetic disposition of a series of perforin-inhibitors as potential immunosuppressive agents

Abstract: The cytolytic protein perforin is a key component of the immune response and is implicated in a number of human pathologies and therapy-induced conditions. A novel series of small molecule inhibitors of perforin function have been developed as potential immunosuppressive agents. The pharmacokinetics and metabolic stability of a series of 16 inhibitors of perforin was evaluated in male CD1 mice following intravenous administration. The compounds were well tolerated 6 h after dosing. After intravenous administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…13,14 The first systemic pharmacokinetic study of small molecule perforin inhibitors revealed that the in vivo clearance of the studied inhibitors was very high as they were prone to phase I metabolic reactions, although the redoxmetabolism did not completely explain fast clearance. 15 Therefore, if the perforin inhibitors are rapidly cleared from the body, they may be unable to reach their target sites at therapeutically relevant concentrations. In addition, to reach their site of action, drugs intended for the treatment of central nervous system disorders have to cross the blood−brain barrier.…”
mentioning
confidence: 99%
“…13,14 The first systemic pharmacokinetic study of small molecule perforin inhibitors revealed that the in vivo clearance of the studied inhibitors was very high as they were prone to phase I metabolic reactions, although the redoxmetabolism did not completely explain fast clearance. 15 Therefore, if the perforin inhibitors are rapidly cleared from the body, they may be unable to reach their target sites at therapeutically relevant concentrations. In addition, to reach their site of action, drugs intended for the treatment of central nervous system disorders have to cross the blood−brain barrier.…”
mentioning
confidence: 99%
“…Our results indicate that the absence of perforin in CTLs is sufficient to protect NOD mice from autoimmune diabetes. This is important for potential translation to prevention of CTL‐mediated beta cell destruction in humans using perforin inhibitors 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…This is important for potential translation to prevention of CTL-mediated beta cell destruction in humans using perforin inhibitors. 19,20 TCR transgenic NOD8.3 mice, in which beta cell destruction is dependent on CTLs, develop diabetes in the absence of perforin. 8 In contrast, perforin-deficient NOD mice, with a polyclonal CTL pool, have less diabetes and insulitis.…”
Section: Discussionmentioning
confidence: 99%
“…The similar activity is demonstrated by derivatives possessing a carboxymethylene group at N‐3 position and arylidene or heteroarylmethylidene group at C‐5 position . Furthermore, derivatives of another five‐membered system, containing exocyclic sulfur atom, possess similar biological properties . These compounds are based on 2‐thioxo‐4‐imidazolidinone system and are called thiohydantoins.…”
Section: Introductionmentioning
confidence: 91%